2022
DOI: 10.2174/1570159x19666211202124925
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Alzheimer’s-like Pathology by Minocycline via Inhibiting Cdk5/p25 Signaling

Abstract: Background: Minocycline has multiple neuroprotective roles in abundant brain diseases, including the prevention and treatment of Alzheimer’s disease (AD). Cdk5/p25 signaling plays an important role in the onset and development of Alzheimer’s-like pathology. The aim of the present work was to further explore the underlying mechanism which minocycline effects on Cdk5/p25 signaling related to the Alzheimer’s-like pathology. Methods: The cognitive function of animals was measured by the Morris water maze test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Therefore, the results of Co‐IP (Figure 3B) demonstrated that activation of CB1R cause the formation of p‐Cdk5/p25 complex after oxycodone withdrawal. In line with our study, previous studies showed that abnormal activity of Cdk5/p25 can lead to neurological dysfunction and a variety of neurodegenerative diseases 30,31 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the results of Co‐IP (Figure 3B) demonstrated that activation of CB1R cause the formation of p‐Cdk5/p25 complex after oxycodone withdrawal. In line with our study, previous studies showed that abnormal activity of Cdk5/p25 can lead to neurological dysfunction and a variety of neurodegenerative diseases 30,31 …”
Section: Discussionsupporting
confidence: 92%
“…In line with our study, previous studies showed that abnormal activity of Cdk5/p25 can lead to neurological dysfunction and a variety of neurodegenerative diseases. 30,31 The interest in tau rose sharply when tau was identified as a pathological hallmark in the patient with AD. 32 The association between opioid exposure and Alzheimer's disease has gained more attention, 33,34 but the alterations in tau phosphorylation site induced by oxycodone remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Tau, as an important substrate of CDK5, can be phosphorylated by CDK5, then separates from microtubules and self-aggregates, and finally forms PHFs and insoluble NFTs in neurons [68] . Knockdown of CDK5 in triple transgenic (3xTg) AD mice, as well as inhibition of CDK5 with CDK5 inhibitory peptide in vitro, has been shown to reduce tau hyperphosphorylation and NFT formation [69] . Minocycline alleviates AD-like pathology and improves cognitive impairment by inhibiting the CDK5/p25 signaling pathway [70] .…”
Section: Tau Phosphorylation Inhibitorsmentioning
confidence: 99%
“…Transgenic expression of Cdk5 inhibitory peptide before and after the insult of p25 could both suppress hippocampal tau phosphorylation and neuronal death, improve the cognitive dysfunction of model mice ( Xu et al, 2019 ; Huang et al, 2020 ). Inhibition of Cdk5/p25 complex also reduced hippocampal Aβ production and tau hyperphosphorylation, improved learning and memory abilities of AD model mice ( Zhao et al, 2021 ).…”
Section: Cyclin-dependent Kinases 5: a Culprit In Neurological Disordersmentioning
confidence: 99%